Narrative and Ideology in the Novel Dream of the Red Chamber: A Critical Analysis - Andi Widiono (Universitas Negeri Surabaya, 2026)
This study aims to examine the narrative and ideology contained in the classic Chinese novel Dream of the Red Chamber by Cao Xueqin through a critical analysis approach. This novel is a monumental literary work that not only presents the story of the life of an aristocratic family, but also reflects the social structure, cultural values, and ideology that developed during the Qing Dynasty. The research method used is descriptive qualitative with text analysis techniques. Data in the form of narrative excerpts containing ideological elements in the novel are analyzed using a literary criticism approach that focuses on the relationship between text, power, and social structure. The results show that the narrative in Dream of the Red Chamber contains various ideologies, such as feudalism, patriarchy, and Confucian values ​​​​that dominate the lives of the characters. In addition, there is an implicit criticism of the rigid social system through the depiction of internal conflict, gender inequality, and the decline of aristocratic families. The narrative constructed not only functions as a storytelling medium, but also as a means to represent and simultaneously question the ideology that prevailed in Chinese society at that time. Thus, this study confirms that Dream of the Red Chamber is a literary work rich in ideological content and critical of social reality. This study is expected to contribute to the development of literary studies, particularly in understanding the relationship between narrative and ideology in classical Chinese literature.